This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple standard approach.
x → 0 lim x sin x = x → 0 lim sin x x = 1
Why is the first equality true?
You can't just flip a limit upside down because it goes to 0 0 :
x → 0 lim x x 3 = x → 0 lim x 3 x
It's better to apply L'Hopital's Rule.
come to slack.
Lol! Look this question.
Log in to reply
Yeah! I got inspired by your problem ⌣ ¨
Log in to reply
Hahaha thanks!
Lim as x-->0 x/sinx = lim as x-->0 1/(sinx/x)= 1/1 = 1
Problem Loading...
Note Loading...
Set Loading...
The limit goes to 0 0 so we may use L'Hopital's Rule:
x → 0 lim x sin x = x → 0 lim 1 cos x = 1